Deterioration of Seed Quality in Mung bean by Macrophomina phaseolina (Tassi) Goid. and its Management - A.K. KAR; K.C. SAHU (Seed Research, 2026)
Macrophomina phaseolina (Tassi) Goid., an important pathogen was associated with 0.8-4.9 per cent seed infection in infected samples of mung bean. Seed infection caused 18.9-31.0 per cent reduction in germination and 13.4-28.0 per cent reduction in seedling length in different varieties. Seed inoculation resulted in 65 to 72.6 per cent seedling emergence in mung bean with incidence of 5.4-13.2 per cent seedling blight and 16.5-32.8 per cent (PDI) of leaf blight. Variety T-44 showed minimum disease incidence and variety K-851 showed the maximum incidence. Out of six fungicides tested, carbendazim was the most effective resulting maximum germination percentage and seedling length with minimum disease incidence. Benomyl was also at par with carbendazim, followed by thiram in managing the seed-borne infection of the pathogen.